Education as Framed Sense-Making - Hasse Møller; Signe Smedegaard Skov (University of Huddersfield Press, 2021)
Building on domain-specific theories and a case study on play and higher education (Møller, 2020), we developed a 'Frame-Pedagogy' design: a model that fuses views on education and play by focusing on their common denominators: framing and sense-making. It explores the connection between play and higher education through three perspectives on educational experience: Academic content as fact, as toy and as tool. We tested and adapted our design by exploring it across two months on a teacher training course. In this paper, we present both iterations of the model as well as student accounts on their perceived meaning and learning outcome related to the course. We conclude that a multiple-frame-approach to education that includes play holds great potential for corresponding with the needs of future professional settings.